The Influence of Technological Factors of the Bimetallic Ribbed Tube Manufacturing Process on the Heat Transfer Rate of Air-Cooling Units - A. B. Sukhotski; V. B. Kuntysh (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article presents an experimental study of the dependence of the heat transfer rate of a six-row staggered bundle made of bimetallic ribbed tubes on the technological factors of manufacturing a cold-rolled ribbed aluminum shell on a supporting tube. The bundle was installed in a wind tunnel and washed by a forced perpendicular air flow. To measure heat transfer, a local thermal modeling method was applied using an electrode calorimeter tube of a fluidized type installed in the middle of the third and fifth transverse rows of the bundle. The experimental data were presented in the form of dependences of the Nusselt and Euler numbers on the Reynolds numbers. Also, thermal contact resistance (the inverse value of thermal conductivity during thermal contact) and the length of the air gap in the contact zone between the aluminum shell and the bearing tube of a bimetallic ribbed tube were experimentally studied. Due to experimental studies, it was found that the lubricating and cooling liquid on the surface of rolled aluminum ribs of bimetallic ribbed tubes does not worsen the rate of heat transfer and the aerodynamic resistance of the bundles of the heat exchange section of air-cooling units. The presence of additional crimping discs in cold rolling mills for ribbed tubes increases heat transfer by 8–13 %. At the same time, the extrusion force cannot be accepted as the main criterion for assessing the quality of connecting the shell of bimetallic ribbed tubes, as is customary in the industry at present. The value of the relative length of the air gap more objectively characterizes the state of contact between the main tube and the ribbed shell, but its use as a determining parameter in express quality control of bimetallic tubes is impossible due to the laboriousness of its calculation. In the contact zone of bimetallic ribbed tubes, any medium with a thermal conductivity coefficient greater than that of air reduces the thermal contact resistance and is an intensifying factor of heat transfer. Due to the thermal characteristics of bimetallic ribbed tubes of air-cooling units, it is impractical to remove presservative grease or other oil from the outer surface of the bearing tubes.